PROBLEM-BASED LEARNING MODEL IN ACHIEVEMENT OF COMPETENCE OF NURSING STUDENTS DURING THE COVID-19 PANDEMIC - Abidin, Zainal; Fibriansari, Rizeki Dwi; Astuti, Anggia (Nurse and Health: Jurnal Keperawatan, 2023)
Background: A new policy has occurred in the world of education due to the impact of the COVID-19 pandemic, which has changed learning that must come to a class or a building or campus, to become independent learning, including nursing students. In this case, they are still required to have abilities by existing competency standards, including cognitive, affective, and psychomotor abilities that can be achieved by applying case-based learning and project-based learning models. Objectives: Find out the problem-based learning model in the competency achievement of nursing students during the COVID-19 pandemic. Methods: The research method used is analytic observational with a case-control approach. The variables in this research are teaching methodology as an independent variable and competency achievement as a dependent variable. The research was conducted for 5 months at the Diploma Nursing Study Program, Faculty of Nursing, Universitas Jember. The data collection technique in this study was by using an instrument in the form of Nursing Clinical Exercise (NCEx). The research respondents were Diploma Nursing Study Program Students with a total of 101 treatment groups with the criteria of having passed in 2022. Results: The research results show that learning models based on Case case-based learning and project-based learning are very important to develop in the classroom, laboratory, and clinical learning where students need real conditions about real cases that require direct identification and recognition. The use of PjBL may lead to improved competency achievement among nursing students. This could be reflected in higher scores on competency assessments, better clinical performance, and a deeper understanding of nursing concepts. Students also really need to be in real contact with nursing cases, especially the conditions of the COVID-19 pandemic which is a challenge for educators and students in the world of health. Conclusion: The problem-based learning method is very helpful for students in meeting the competency targets for graduates of the third diploma in nursing.